BOOK-TAX DIFFERENCE, EARNINGS MANAGEMENT AND BOND RATINGS IN THE BRAZILIAN MARKET - Miiller, Diego Lopes; Martinez, Antonio Lopo (Revista Universo Contábil, 2016)
This article investigates whether the credit rating of bond issues in the Brazilian market is influenced by the differences between book income and taxable income (BTD), as well earning management practices, based on a sample of all nonfinancial firms that issued bonds in the period from 2004 to 2014 with published financial information, resulting in a final sample of 96 observations. The results indicate BTD does not determine the credit rating in the Brazilian market. Additionally, we tested the influence on credit rating of propensity for earnings management (EM) and tax management (TM). The results indicate as earnings management increases, ratings tend to decline, while firms that engage in aggressive tax management are not penalized. The study of this phenomenon can help to predict the credit rating in Brazil, and would allow identifying factors that affect it and actions to reduce the perception of risks to solvency, and consequently the cost of debt.